Comparison of serum SDMA and creatinine as a biomarker for the detection of meloxicam-induced kidney injury in cats - Wun, Matthew K.; Broughton-Neiswanger, Liam E.; Villarino, Nicolas F. (Frontiers in Veterinary Science, 2024)
Introduction Serum symmetric dimethylarginine (SDMA) and creatinine are commonly used biomarkers of renal function in cats. We hypothesize that the serum analytes creatinine and SDMA are equally effective at detecting impaired renal function caused by meloxicam-induced renal injury in cats. Our primary objective was to compare serum concentrations of SDMA and creatinine in cats before, during, and after induction of renal injury from repeated dosages of meloxicam in the context of a small pilot study. Methods This follow-up study results from data collected in a well-controlled study that included 12 healthy female adult purpose-bred cats. Cats in the treatment group received meloxicam 0.3 mg/kg subcutaneously (SC) every 24 h for 31 days. Cats in the control group received saline (0.1 mL SC). Renal injury was defined as the presence of tubular damage, basement membrane damage, and/or interstitial inflammation in histological sections of kidney tissue. Serum creatinine and SDMA concentration were measured every 4 days. Results In the control group, no cats developed renal azotemia. In the treatment group, four out of six cats developed elevated serum creatinine and histopathological evidence of renal injury. Three of these cats developed an elevation in serum SDMA. The time to the development of renal azotemia using serum creatinine or SDMA was not significantly different (p > 0.05). Discussion In this pilot study, there was no evidence that serum SDMA was superior to serum creatinine at detecting impaired renal function caused by meloxicam-induced renal injury in cats.